The complete mitochondrial genome sequence of the fairy ring-forming fungus Lepista sordida. Issue 4 (3rd April 2022) - Choi, Jae-Hoon; Suzuki, Tomohiro; Ono, Akiko; Kotajima, Mihaya; Tanaka, Yuki; Suzuki, Toshiyuki; Kawagishi, Hirokazu; Dohra, Hideo
Abstract: Lepista sordida is a fairy ring-forming fungus that belongs to the family Tricholomataceae and is widely distributed in the Northern Hemisphere. Here, we report the complete mitochondrial genome sequence of L. sordida . The mitochondrial genome (57, 375 bp) contained 20 protein-coding genes, 2 ribosomal RNA genes, and 26 transfer RNA genes. Phylogenetic analysis based on 14 conserved protein sequences from L. sordida and 15 related basidiomycetes showed that L. sordida was located on the outermost branch of the Tricholomataceae clade. This study is the first to report the complete mitochondrial genome sequence of a fairy ring-forming fungus belonging to the genus Lepista.